EFFECTS OF RISING COST OF PRODUCTION ON SALES OF ALCOHOLIC BEVERAGES IN NIGERIA - Okorozoh, Ugochukwu Lawrence (African Journal of Social and Behavioural Sciences, 2025)
This research investigated the relationship between rising production costs and sales of alcoholic beverages in selected South East Nigerian brewery firms. Employing a simple linear correlation design, the study targeted management and staff from these firms, comprising a population of 750 individuals. Using Slovin’s formula, a sample size of 261 was calculated; however, the sample consisted of 236 respondents, yielding a remarkable 90.4% response rate. These results indicated high reliability, confirming the instrument’s suitability for the study. The dataset underwent initial normality testing using the Anderson-Darling Statistic, confirming that the residual term met the normality assumption for bivariate datasets. Additionally, multicollinearity checks revealed no issues for multiple datasets. These favourable results justified the application of parametric regression analysis. To address the research questions, Pearson correlation coefficients were computed to examine the relationships between dependent and independent variables. Subsequently, regression analysis was employed to test the hypotheses, assessing the significance and strength of these relationships. IBM SPSS version 28.0 and Minitab software version 20.0 packages were employed for ease of analysis. The results showed significant positive relationships between rising production costs and sales volume, purchasing frequency, and consumer loyalty. The study recommended, among others that cost-efficient strategy, pricing decisions, and loyalty programs to maintain competitiveness. The findings contributed to the understanding of production cost management in the South-East Nigerian alcoholic beverage industry.